2013
DOI: 10.9790/0853-0440709
|View full text |Cite
|
Sign up to set email alerts
|

Does Maternal Education Really Improve Child Health?

Abstract: Maternal education plays an important role in determination of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Unlike maternal education, high level of paternal education was found to be a protective factor of child hospitalization. In line with the current results, other studies reported that maternal education does not influence the incidence of child morbidity and mortality [53], [54]. Interestingly, Sudan Household Health Survey 2000 revealed a positive correlation between maternal education and incidence of diarrheal diseases, that is, high maternal education level associated with a high rate of diarrheal diseases [41].…”
Section: Discussionsupporting
confidence: 89%
“…Unlike maternal education, high level of paternal education was found to be a protective factor of child hospitalization. In line with the current results, other studies reported that maternal education does not influence the incidence of child morbidity and mortality [53], [54]. Interestingly, Sudan Household Health Survey 2000 revealed a positive correlation between maternal education and incidence of diarrheal diseases, that is, high maternal education level associated with a high rate of diarrheal diseases [41].…”
Section: Discussionsupporting
confidence: 89%
“…Mothers’ level of education appeared to have a major effect on early language development not only in normal children but also in children with autism spectrum disorder (ASD) [28]. We thought that maternal education not only can affect language development directly through maternal vocabulary input but also indirectly through choosing appropriate feeding practices [46] and providing a health care and a safe environment for their children [47].…”
Section: Discussionmentioning
confidence: 99%
“…This study did not find a significant relationship between the paternal education level and nutrition literacy level, but there is a significant relationship between the maternal education level with interactive nutrition literacy level and critical nutrition literacy level. A mother's education level is more related to nutrition literacy than a father's level of education, which can be caused because mothers with higher education have better knowledge about health and nutrition [42]. Mothers in the family also play a role as providers of health and nutrition in the household and the mother's education is also related to the nutritional status of children in the family [43].…”
Section: Methodsmentioning
confidence: 99%